Dental Anxiety Among Undergraduate Students of the University of the Philippines Manila During the Time of the COVID-19 Pandemic/Ghazaleh S. Baghban, Diana Frances C. Mulles and Ezekiel Christian C. Ong. - Bagbhan, Ghazaleh S.; Mulles, Diana Frances C.; Ong, Ezekiel Christian C.
Objectives: This study aims to determine the prevalence and reasons for dental anxiety (DA), as well as changes in their oral health-seeking behavior among undergraduate students of the University of the Philippines Manila (UPM) during the time of the COVID-19 pandemic.